2011
DOI: 10.1177/0192623311406934
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Xenobiotic-Induced Hepatocellular Enzyme Induction in Rats

Abstract: During routine safety evaluation of RO2910, a non-nucleoside reverse transcriptase inhibitor for HIV infection, histopathology findings concurrent with robust hepatocellular induction occurred in multiple organs, including a unique, albeit related, finding in the pituitary gland. For fourteen days, male and female rats were administered, by oral gavage vehicle, 100, 300, or 1000 mg/kg/day of RO2910. Treated groups had elevated serum thyroid-stimulating hormone and decreased total thyroxine, and hypertrophy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 30 publications
2
34
0
1
Order By: Relevance
“…Total (combined "weak" and "dark") TSH-positive areas presented no correlation to the hypertrophy scoring (data not shown), which indicated the lack of increase in the total TSH-immunoreactive cell population in the pituitary par distalis. An absence of hyperplasia (i.e., cell proliferation) in the pituitary gland was further supported by the lack of an RO2910-related increase in topoisomerase II immunoreactivity and thus of mitotic activity, as reported previously (Zabka et al 2011).…”
Section: Quantification Of Individual Cell Hypertrophy In Pituitary Gsupporting
confidence: 80%
See 2 more Smart Citations
“…Total (combined "weak" and "dark") TSH-positive areas presented no correlation to the hypertrophy scoring (data not shown), which indicated the lack of increase in the total TSH-immunoreactive cell population in the pituitary par distalis. An absence of hyperplasia (i.e., cell proliferation) in the pituitary gland was further supported by the lack of an RO2910-related increase in topoisomerase II immunoreactivity and thus of mitotic activity, as reported previously (Zabka et al 2011).…”
Section: Quantification Of Individual Cell Hypertrophy In Pituitary Gsupporting
confidence: 80%
“…1B). Refining the semi-quantitative histological interpretation, quantification demonstrated a statistically significant increase in all but the group 2 females and distinguished a dose-dependent response (Zabka et al 2011).…”
Section: Quantification Of Liver Hypertrophy and Correlation With Hismentioning
confidence: 94%
See 1 more Smart Citation
“…Most recently, an in vivo study reported that rats underwent significant thyroid gland weight gain when exposed to MP and BP doses of 1000 mg/kg BW/day (Vo et al, 2010). Such a weight change might be explained by activation of a feedback loop in response to low TH blood levels, stimulating the thyroid gland to produce more THs and potentially leading to hypertrophy and corresponding increase in thyroid gland weight (Zabka et al, 2011). The same study by Vo et al (2010) also demonstrated that exposure to doses ranging from 62.5 to 1000 mg/kg BW/day of MP, PP, isopropyl paraben, and isobutyl paraben significantly diminished T4 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Following the OeCD tG 407 which includes endpoints for thyroid hormone disruption, Higashihara et al found effects on thyroid hormone level in addition to changes in thyroid and pituitary weight (Higashihara et al, 2007). While the exact mechanism of action is not yet elucidated, BPF did not affect cell proliferation in both the t-screen and the tSH-screen, suggesting that its main mechanism of acwith other pathways (Roy and Mugesh, 2006b;Cao et al, 2010;Gayrard et al, 2011;Zabka et al, 2011;Kosuda et al, 1997;Grover et al, 2007;liu and Brent, 2010). thus, with the exception of t4 and tSH, the effects of the selected thyroid-active compounds on pituitary and thyroid organ weights in vivo are not likely to be due to a direct effect on cell proliferation.…”
Section: Discussionmentioning
confidence: 99%